THE ADOPTION OF NEW PARADIGM: INNOVATION OF VIRTUAL REALITY (VR) MODEL LEARNING BASED ON CULTURAL HERITAGE OF BANDAR SENAPELAN TO ASSIST STUDENTS IN EDUCATION - Suroyo, Suroyo; Putra, Bima Maulana; Al-Fiqri, Yanuar; Ibrahim, Bedriati; Pratama, M. Noval Dwi (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Some previous studies show that the impact of the Covid-19 on the tourism sector is very influential on the decline of tourists both local and international to travel between regions. Bandar Senapelan (which is now a Kampung Bandar Village) has historical objects such as Tuan Khadi, Istana Hinggap, Masjid Raya, Marhum Mosque, Pelindo Port, Pekanbaru Kilometer Zero Port (before moving to Tugu Zapin) and several other historical attractions. The concept of virtual reality (VR) can represent and provide information on the historic city of Bandar Senapelan for local and international restrictions. This virtual reality (VR) provides benefits for tourists and the wider community because it can save costs, the time to simulate an object visited. This is a reason for researchers to design a virtual reality (VR) model at the dealer of Senapelan as a historical tour that puts forward "local heritage" so that it becomes a historical tourist attraction for the wider community to travel virtual during the Pandemic Covid-19 period. The Virtual Reality (VR) model can communicate about the dealer of Senapelan to tourists and the wider community. The method used in this study is Research and Development also known as research/design and development research.